Study of the effect of adding topical Nepafenac 0.1% eye drop on increasing mydriasis in patients with diabetes mellitus type 2 - Sabbagh, Micheal Thamin; Rajab, Mahamoud; Jalloul, Kahtan (Journal of medical and pharmaceutical sciences, 2022)
Objective: To evaluate the effect of adding topical Nepafenac 0.1% eye drop on increasing mydriasis in patients with Diabetes Mellitus type 2.Methods: the study was conducted on 73 eyes of 73 patients who had type 2 diabetes for 5 years or more. The pupil diameter (PD) was measured in the both eyes without dilation using an Autorefractokeratometer (Grand Seiko\GR- 3500 Ka), then the pupils were dilated in the both eyes using topical Tropicamide 1%. A second measurement of (PD) was taken after dilating using the same device. Topical Nepafenac 0.1% were prescribed 3 times a day for 3 days in the right eye. During the review, after 3 days, the pupils were dilated using topical Tropicamide 1%. A third measurement of the (PD) of the both eyes was taken after dilation using the same device. The efficacy of Nepafenac 0.1% was evaluated by determining the increase in (PD) in the eye that received topical Nepafenac 0.1% and comparing it with the other eye that did not receive.Results: The mean diameter of the pupil in the right eye after dilation was 4.68±0.8 mm and in the left eye was 4.67±0.7 mm (P=0.8). After applying Nepafenac 0.1% topically 3 times a day in the right eye for 3 days, the mean diameter of the pupil in the right eye after dilation was 6.50 ± 0.9 mm and in the left eye 5.10± 0.08 mm (P=0.001). The change in the mean diameter of the pupil in the right eye was 1.82 ± 0.7 mm, and in the left eye was 0.43 ± 0.6 mm.Conclusion: Topical application of Nepafenac 0.1% showed an increase in pupillary diameter after dilation with Tropicamide 1% in patients with type 2 diabetes mellitus.
Keywords: Non- steroid anti-inflammatory drugs; mydriasis; Tropicamide 1%; Sympathetic innervation; Para Sympathetic innervation; Nepafenac 0.1%,